Jenseits der Schriftkultur $1 (BBand 1s - Nadin, Mihai, 1938- (Salt Lake City, UT : Project Gutenberg, 2003)
"Jenseits der Schriftkultur $1 (BBand 1" by Mihai Nadin is a philosophical and sociocultural exploration written in the late 20th century. The book delves into the phenomenon of the decline of written culture and the concurrent rise of alternative forms of communication and interaction in an increasingly digital and interconnected world. Nadin examines the implications of this shift for various aspects of human experience, including education, politics, and personal identity. The opening of the book sets the stage for a critical examination of how contemporary society navigates the tension between traditional written culture and emerging forms of expression and interaction. The author draws a vivid contrast between historical figures like Melanchthon, who embodied the values of a literate society, and modern characters such as Zizi, who symbolize a more fragmented, yet pragmatically engaged, way of life. Through these examples, Nadin raises significant questions about literacy, knowledge, and the evolving nature of communication, arguing that the rapid pace of information production and cultural change marks a transformative period in human history. This introduction not only foreshadows the book's broader themes but also invites readers to consider how they fit into this shifting landscape. (This is an automatically generated summary.)s
Release date is 2003-08-01
Produced by Michael Pullen
Keywords: Literacy -- Social aspects; Sociolinguistics; Technology and civilization; Technology -- Social aspects; Computers and literacy; Social history; Information society; Oral history